Strengthening Civic Education Through Multidisciplinary Collaboration (PKn-Sociology): Examining the Impact of Globalization on National Identity Among Adolescents - Tetep, Tetep; Setiawan, Yayan; ., Hendiyansyah; Sarippudin, Ujang; Sudarmanto, Resty Istiarti; Hardiyanti, Tri Widi; ., Inaiyah Widi; Amelia, Liska; Nurhasanah, Sopia Widi; Suryanto, Rendi Widi (Indonesian Journal of Community Empowerment (IJCE), 2025)
This community service program, titled "Strengthening Citizenship Education through Multidisciplinary Collaboration (PKn-Sociology): Examining the Impact of Globalization on National Identity Among Adolescents," was successfully implemented at SMAN 2 Garut. The program involved 131 adolescents aged 15-18 and aimed to enhance their understanding of globalization's influence on national identity. Employing a participatory and collaborative approach across preparatory, implementation, and evaluation phases, the initiative developed an interactive PKn-Sociology module. Quantitative results from pre-test and post-test scores revealed a significant 21% increase in participants' understanding of globalization, national identity, and digital literacy. Qualitatively, focused group discussions indicated heightened critical thinking in filtering digital information and a stronger appreciation for local cultural values. The program also fostered the creation of tangible outputs like digital posters and short educational videos, showcasing adolescents' transition into proactive agents of positive change. These findings affirm the effectiveness of multidisciplinary collaboration in equipping adolescents with robust national identity in the digital age.